Broadband Vibrational Energy Harvesting Based on a Triboelectric Nanogenerator. Issue 6 (27th November 2013) - Yang, Jin; Chen, Jun; Yang, Ya; Zhang, Hulin; Yang, Weiqing; Bai, Peng; Su, Yuanjie; Wang, Zhong Lin
<x xml:space="preserve">Abstract</x> Vibrations in living environments are generally distributed over a wide frequency spectrum and exhibit multiple motion directions over time, which renders most of the current vibration energy harvesters unpractical for their harvesting purposes. Here, a 3D triboelectric nanogenerator (3D‐TENG) is designed based on the coupling of the triboelectrification effect and the electrostatic induction effect. The 3D‐TENG operates in a hybridization mode of conjuntioning the vertical contact‐separation mode and the in‐plane sliding mode. The innovative design facilitates harvesting random vibrational energy in multiple directions over a wide bandwidth. An analytical model is established to investigate the mechano‐triboelectric transduction of 3D‐TENG and the results agree well with experimental data. The 3D‐TENG is able to harvest ambient vibrations with an extremely wide working bandwidth. Maximum power densities of 1.35 W m‐2 and 1.45 W m‐2 are achieved under out‐of‐plane and in‐plane excitation, respectively. The 3D TENG is designed for harvesting ambient vibration energy, especially at low frequencies, under a range of conditions in daily life and has potential applications in environmental/infrastructure monitoring and charging portable electronics.